Regulatory T cells that co-express RORγt and FOXP3 are pro-inflammatory and immunosuppressive and expand in human pancreatic cancer. (2nd April 2016) - Chellappa, Stalin; Hugenschmidt, Harald; Hagness, Morten; Line, Pål D.; Labori, Knut J.; Wiedswang, Gro; Taskén, Kjetil; Aandahl, Einar M.
ABSTRACT: Pancreatic ductal adenocarcinoma (PDAC) is highly infiltrated by CD4 + T cells that express RORγt and IL-17 (TH 17). Compelling evidence from the tumor microenvironment suggest that regulatory T cells (Treg ) contribute to TH 17 mediated inflammation. Concurrently, PDAC patients have elevated levels of pro-inflammatory cytokines that may lead to TH 17 associated functional plasticity in Treg . In this study, we investigated the phenotype and functional properties of Treg in patients with PDAC. We report that PDAC patients have elevated frequency of FOXP3 + Treg, which exclusively occurred within the FOXP3 + RORγt + Treg compartment. The FOXP3 + RORγt + Treg retained FOXP3 + Treg markers and represented an activated subset. The expression of RORγt in Treg may indicate a phenotypic switch toward TH 17 cells. However, the FOXP3 + RORγt + Treg produced both TH 17 and TH 2 associated pro-inflammatory cytokines, which corresponded with elevated TH 17 and TH 2 immune responses in PDAC patients. Both the FOXP3 + Treg and FOXP3 + RORγt + Treg from PDAC patients strongly suppressed T cell immune responses, but they had impaired anti-inflammatory properties. We conclude that FOXP3 + RORγt + Treg have a dual phenotype with combined pro-inflammatory and immunosuppressive activity, which may be involved in the pathogenesis of PDAC.